2007
DOI: 10.1016/j.str.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a k/k0 Method to Identify Long-Range Structure in Transition States during Conformational Folding/Unfolding of Proteins

Abstract: A previously introduced kinetic-rate constant (k/k(0)) method, where k and k(0) are the folding (unfolding) rate constants in the mutant and the wild-type forms, respectively, of a protein, has been applied to obtain qualitative information about structure in the transition state ensemble (TSE) of bovine pancreatic ribonuclease A (RNase A), which contains four native disulfide bonds. The method compares the folding (unfolding) kinetics of RNase A, with and without a covalent crosslink and tests whether the cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In contrast to the expectation from the chain entropy model, the increase in stability (∆T m = +4.9 °C and +2.2 °C, respectively) was found to result mainly from a decrease in k U in both variants. More recently, Pradeep et al [40] have studied the same variants in guanidine hydrochloride (GdnHCl) and confirmed the decrease of k U observed under thermal denaturation. While no change in k f was found for V43C/R85C-RNase A (confirming the expectations from thermal denaturation), folding of A4C/V118C-RNase A was found to be decelerated by almost the same extent as k U .…”
mentioning
confidence: 75%
“…In contrast to the expectation from the chain entropy model, the increase in stability (∆T m = +4.9 °C and +2.2 °C, respectively) was found to result mainly from a decrease in k U in both variants. More recently, Pradeep et al [40] have studied the same variants in guanidine hydrochloride (GdnHCl) and confirmed the decrease of k U observed under thermal denaturation. While no change in k f was found for V43C/R85C-RNase A (confirming the expectations from thermal denaturation), folding of A4C/V118C-RNase A was found to be decelerated by almost the same extent as k U .…”
mentioning
confidence: 75%
“…The refolding kinetics were acquired on a log-time base in which the acquisition is faster on the millisecond time scale and slower on the second time scale, thereby allowing accurate measurements to be taken in the fast kinetics regime. The procedure described previously (21) was used to minimize viscosity effects and thereby ensure proper mixing at the cost of an increase in the dead time. An increase in the dead time did not give rise to any burst-phase kinetics since the mixings were carried out at 15 °C.…”
Section: Methodsmentioning
confidence: 99%